Responsible Business Practices and Legal and Practical Issues in Corporate Governance and Investment in Vietnam - Thanh Thuy, Phan Thi (VNU Journal of Science: Legal Studies; Vol 40 No 2, 2024)
Responsible business practices (RBP) is a national and global strategy, but it is not a completely new concept in the world and in Vietnam. It is the proactive development and practice of corporate social responsibility (CSR) nationally and internationally. Accordingly, RBP is to promote enterprises to comply with the law, respect people's interests, and protect the environment and social benefits. In Vietnam, except for the domestic enterprises in the partner network of large foreign corporations, the awareness and practice of CSR have not become a popular movement among small and medium-sized enterprises. Therefore, in parallel with building a comprehensive and mandatory business legal framework, education to raise the awareness and practice of CSR for domestic enterprises would create a suitable environment for ensuring RBP in the Vietnam.